Konsep Meminta Maaf Sebagai Hukuman Dalam Perkara Pidana - Amdani, Yusi; Krisna, Liza Agnesta (Jurnal Hukum IUS QUIA IUSTUM, 2019)
Criminalization  is  an  act  against  a  criminal,  but  many  criminal  cases  are  completed  as  a  result  of  theimplementation  of  peace  by  apologizing.  This  research  focuses  on  the  following  problems:  first,  how  the reconceptualization of apologizing as the part of the punishment is reviewed in accordance with the positive law and Islamic law, and second, how the realization of the concept of apoligizing as a punishment in a criminal case is. The research method used in this study is normative juridical. From the results of the study, it can be concluded that, first, the concept of apologizing is known in criminal law and Islamic law. Regarding the virtue of Islamic law, the concept of apologizing is able to eliminate the criminal acts; thus, the value of the apologizing concept in Islamic law can be applied in criminal law. In national criminal law, the concept of apologizing is implicitly accommodated in the peace process, which in certain criminal acts, especially in the category of minor criminal  offenses,  is  permitted  to  make  peace.  Second,  some  cases  that  can  be  given  peace  are  also determined for certain cases such as accidents in traffic, crimes committed by underage child, and other acts constituting the minor crimes by the category of complaint offenses.